2010
DOI: 10.1073/pnas.1012076108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of RNA stabilization and translational activation by a pentatricopeptide repeat protein

Abstract: Pentatricopeptide repeat (PPR) proteins comprise a large family of helical repeat proteins that bind RNA and modulate organellar RNA metabolism. The mechanisms underlying the functions attributed to PPR proteins are unknown. We describe in vitro studies of the maize protein PPR10 that clarify how PPR10 modulates the stability and translation of specific chloroplast mRNAs. We show that recombinant PPR10 bound to its native binding site in the chloroplast atpI-atpH intergenic region (i) blocks both 5′→3′ and 3′→… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
352
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(387 citation statements)
references
References 49 publications
21
352
0
2
Order By: Relevance
“…Fisk et al (1999) first reported a maize PPR gene, (for CHLOROPLAST RNA PROCESSING1), which was implicated by genetic analysis in processing and translation of plastid pet transcripts. Similar effects on plastid transcripts were subsequently observed in other mutants from Arabidopsis (Hashimoto et al, 2003;Meierhoff et al, 2003;Yamazaki et al, 2004;ChateignerBoutin et al, 2008ChateignerBoutin et al, , 2011Chi et al, 2008;Okuda et al, 2009Okuda et al, , 2010Yu et al, 2009;Johnson et al, 2010), rice (Kazama and Toriyama, 2003;Komori et al, 2004;Gothandam et al, 2005), and maize (Williams and Barkan, 2003;Schmitz-Linneweber et al, 2006;Pfalz et al, 2009;Prikryl et al, 2011). Additional evidence for a role of PPR proteins in regulating organelle gene expression has also come from positional cloning of several cytoplasmic male sterility (CMS) restorer genes from petunia (Petunia hybrida; Bentolila et al, 2002) and radish (Raphanus sativus; Brown et al, 2003;Desloire et al, 2003;Koizuka et al, 2003).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Fisk et al (1999) first reported a maize PPR gene, (for CHLOROPLAST RNA PROCESSING1), which was implicated by genetic analysis in processing and translation of plastid pet transcripts. Similar effects on plastid transcripts were subsequently observed in other mutants from Arabidopsis (Hashimoto et al, 2003;Meierhoff et al, 2003;Yamazaki et al, 2004;ChateignerBoutin et al, 2008ChateignerBoutin et al, , 2011Chi et al, 2008;Okuda et al, 2009Okuda et al, , 2010Yu et al, 2009;Johnson et al, 2010), rice (Kazama and Toriyama, 2003;Komori et al, 2004;Gothandam et al, 2005), and maize (Williams and Barkan, 2003;Schmitz-Linneweber et al, 2006;Pfalz et al, 2009;Prikryl et al, 2011). Additional evidence for a role of PPR proteins in regulating organelle gene expression has also come from positional cloning of several cytoplasmic male sterility (CMS) restorer genes from petunia (Petunia hybrida; Bentolila et al, 2002) and radish (Raphanus sativus; Brown et al, 2003;Desloire et al, 2003;Koizuka et al, 2003).…”
mentioning
confidence: 65%
“…Attempts to identify the in vivo RNA ligands have only been made for a few PPR proteins (Schmitz-Linneweber and Small, 2008;Okuda et al, 2009Okuda et al, , 2010Pfalz et al, 2009;Yu et al, 2009;Johnson et al, 2010;Chateigner-Boutin et al, 2011;Prikryl et al, 2011). Many of the postulated activities of PPR proteins still lack direct biochemical proof and thus leave open the possibility that their roles are more indirect than suspected and may require additional, unidentified factors.…”
Section: Ysa Encodes a Ppr Protein Essential For Chloroplast Biogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPR protein PPR10 has analogous activities but acts on different chloroplast mRNAs (17). Based on the mechanisms established for PPR10 (18), we hypothesized that the HCF107 binding site maps to the immediate 5′ end of those RNA isoforms that fail to accumulate in its absence and that bound HCF107 blocks 5′ → 3′ RNA degradation. As a first step toward testing this hypothesis, we determined whether rHCF107 binds with specificity to a 26-nt RNA with a 5′ end that maps 2 nt upstream of the HCF107-dependent psbH 5′ terminus.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently shown that PPR binding could induce local RNA structure reorganization to make otherwise hidden binding sites more accessible to other proteins or complexes. 22 The ability of PPR proteins to locally influence RNA secondary or tertiary structures likely explains the large variety of RNA processing steps associated with this class of proteins.…”
Section: Rf-ppr Genes Impede Specifically the Expression Or The Accummentioning
confidence: 99%